CD4 changes among virologically suppressed patients on antiretroviral therapy: a systematic review and meta‐analysis. Issue 1 (7th August 2015) - Ford, Nathan; Stinson, Kathryn; Gale, Howard; Mills, Edward J; Stevens, Wendy; González, Mercedes P; Markby, Jessica; Hill, Andrew
Abstract : Introduction: The effectiveness of antiretroviral therapy (ART) is assessed by measuring CD4 cell counts and viral load. Recent studies have questioned the added value of routine CD4 cell count measures in patients who are virologically suppressed. Methods: We systematically searched three databases and two conference sites up to 31 October 2014 for studies reporting CD4 changes among patients who were on ART and virologically suppressed. No geographic, language or age restrictions were applied. Results and discussion: We identified 12 published and 1 unpublished study reporting CD4 changes among 20, 297 virologically suppressed patients. The pooled proportion of patients who experienced an unexplained, confirmed CD4 decline was 0.4% (95% CI 0.2–0.6%). Results were not influenced by duration of follow‐up, age, study design or region of economic development. No studies described clinical adverse events among virologically suppressed patients who experienced CD4 declines. Conclusions: The findings of this review support reducing or stopping routine CD4 monitoring for patients who are immunologically stable on ART in settings where routine viral load monitoring is provided.